2020
DOI: 10.3390/nu12020561
|View full text |Cite
|
Sign up to set email alerts
|

Net Absorption and Metabolism of β-Hydroxy- β-Methyl Butyrate during Late Gestation in a Pig Model

Abstract: The leucine metabolite, β-hydroxy-β-methyl butyrate (HMB), is widely used in human nutrition and animal production as a nutritional supplement. Although the HMB usage during late gestation has been demonstrated to have a positive effect on fetal development, knowledge on net absorption and metabolism of HMB and impact of HMB on branched chain amino acids (BCAAs) metabolism is lacking. To address this, we conducted a study using pigs during the perinatal period as a model organism. Eight-second parity sows were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
4
1
0
Order By: Relevance
“…In the present study, no statistically significant differences in body weight were found between groups of females supplemented with HMB and those not receiving HMB supplementation, as reported previously [ 41 ], which is also in agreement with some other studies conducted on pigs [ 42 , 43 , 44 ]. Our data also showed that pregnancy did not affect the body weight of the mice immediately after delivery as compared with non-breeding females.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, no statistically significant differences in body weight were found between groups of females supplemented with HMB and those not receiving HMB supplementation, as reported previously [ 41 ], which is also in agreement with some other studies conducted on pigs [ 42 , 43 , 44 ]. Our data also showed that pregnancy did not affect the body weight of the mice immediately after delivery as compared with non-breeding females.…”
Section: Discussionsupporting
confidence: 94%
“…This may mean that if piglets are to receive optimal benefit either late gestation or during lactation that the dose needs to be fed at least twice daily, which if mixed in the complete feed would be compatible with most commercial practices. In the study by Nissen et al, milk HMB levels were increased on day 10 of lactation and, in more recent studies, HMB in colostrum and milk has been shown to increase similarly to the study presented here (Wan et al, 2017;Hu et al, 2020). Additionally, Hu et al (2020) found that 26% of the HMB dosage ended up in the colostrum.…”
Section: Discussionsupporting
confidence: 82%
“…In the study by Nissen et al, milk HMB levels were increased on day 10 of lactation and, in more recent studies, HMB in colostrum and milk has been shown to increase similarly to the study presented here (Wan et al, 2017;Hu et al, 2020). Additionally, Hu et al (2020) found that 26% of the HMB dosage ended up in the colostrum. Wan et al (2017) found that this lactational intake of HMB by the piglets resulted in improved growth characteristics that were carried through to slaughter, weight at 180 days, average daily gain, and a trend for improved feed efficiency.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The daily pattern of HMB intake may influence its effect on the birth weight of progeny. Hu et al [33] studied the absorption and metabolism of HMB fed to pregnant sows once daily. They reported that the net portal flux of HMB peaked at 30 min after a meal and approached zero at about 6 h post prandial.…”
Section: Discussionmentioning
confidence: 99%